Open and Closed Innovation Different Cultures for Different Strategies - Herzog, Philipp; SpringerLink (Wiesbaden Gabler, 2011)
Many firms have shifted from a Closed Innovation to an Open Innovation strategy. During such change, firms often focus on implementing new processes to identify and use external technologies and new markets. Adapting the innovation culture, however, is neglected and results in a nonsatisfying implementation success. Philipp Herzog develops a theoretical framework focusing on differences between Closed and Open Innovation cultures (e.g. NIH syndrome). Based on a multi-respondent survey among R&D employees in the chemical industry, he provides empirical evidence for many of the hypothesized differences in innovation culture. The 2nd revised edition has been completely reviewed and updated.
Innovation and the open innovation concept -- Innovation culture -- Conceptual framework and hypotheses -- Analysis and results -- Discussion of findings and implications for theory and practice
Electronic reproduction.
Keywords: Technological innovations -- Management; Research, Industrial; Electronic books